PENGARUH KOMPETENSI, MOTIVASI, DAN DISIPLIN TERHADAP PRODUKTIVITAS PEGAWAI BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA KABUPATEN DONGGALA - Satiawan, Muhamat (Katalogis, 2016)
The research is aimed to: 1) analyze the simultaneous influence of competency, motivation, and discipline on officials’ productivity in The Agency For Community Empowerment and Village Governance of Donggala Regency; 2) analyze the influence of competency on officials’ productivity in The Agency For Community Empowerment and Village Governance of Donggala Regency; 3) analyze the influence of motivation on officials’ productivity in The Agency For Community Empowerment and Village Governance of Donggala Regency;4) analyze the influence of discipline on officials’ productivity in The Agency For Community Empowerment and Village Governance of Donggala Regency. This research is descriptive  and it involves 57 respondents who selected through census technique. The results  based on multiple linear regressions analysis show that: 1) competency, motivation, and discipline simultaneously have significant influence on officials’ productivity in The Agency For Community Empowerment and Village Governance of Donggala Regency; 2)  competency partially has significant influence on officials’ productivity in The Agency For Community Empowerment and Village Governance of Donggala Regency; 3) motivation partially has significant influence on officials’ productivity in The Agency For Community Empowerment and Village Governance of Donggala Regency; 4) discipline partially has significant influence on officials’ productivity in The Agency For Community Empowerment and Village Governance of Donggala Regency;